2022
DOI: 10.3390/v14051039
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathway Reporter Screen with SARS-CoV-2 Proteins Identifies nsp5 as a Repressor of p53 Activity

Abstract: The dysregulation of host signaling pathways plays a critical role in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and viral pathogenesis. While a number of viral proteins that can block type I IFN signaling have been identified, a comprehensive analysis of SARS-CoV-2 proteins in the regulation of other signaling pathways that can be critical for viral infection and its pathophysiology is still lacking. Here, we screened the effect of 21 SARS-CoV-2 proteins on 10 different host signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The results of KEGG and GO pathway enrichment indicated that those genes were mostly enriched in DNA replication, immunomodulation, and energy metabolism. Increasing studies of COVID-19 patients showed that SARS-Cov-2 infects and replicates in endothelial cells in multiple organs, such as the heart, lung, kidney, and liver ( Dashtban et al, 2022 ; Giovannini et al, 2022 ; John et al, 2022 ; Kumar et al, 2022 ; Schold et al, 2022 ; Zheng et al, 2022 ). In addition, the enriched pathway p53 signaling was identified as a key pathway of genomic stability and cell cycle progression, it even plays a great part in the suppression of viral replication ( Kumar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of KEGG and GO pathway enrichment indicated that those genes were mostly enriched in DNA replication, immunomodulation, and energy metabolism. Increasing studies of COVID-19 patients showed that SARS-Cov-2 infects and replicates in endothelial cells in multiple organs, such as the heart, lung, kidney, and liver ( Dashtban et al, 2022 ; Giovannini et al, 2022 ; John et al, 2022 ; Kumar et al, 2022 ; Schold et al, 2022 ; Zheng et al, 2022 ). In addition, the enriched pathway p53 signaling was identified as a key pathway of genomic stability and cell cycle progression, it even plays a great part in the suppression of viral replication ( Kumar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies of COVID-19 patients showed that SARS-Cov-2 infects and replicates in endothelial cells in multiple organs, such as the heart, lung, kidney, and liver (Dashtban et al, 2022;Giovannini et al, 2022;John et al, 2022;Kumar et al, 2022;Schold et al, 2022;Zheng et al, 2022). In addition, the enriched pathway p53 signaling was identified as a key pathway of genomic stability and cell cycle progression, it even plays a great part in the suppression of viral replication (Kumar et al, 2022). Those augments further explained the genes we explored were hub genes Frontiers in Pharmacology frontiersin.org 10 involved in the pathological course of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was observed that knockout of TP53 gene promoted viral replication, and that, on the opposite, the expression of p53 served as antiviral cellular molecule able to downregulate SARS-CoV replication ( 5 ). More recently, another group, screening the impact of SARS-CoV-2 proteins in several signaling pathways involved in viral infection, has demonstrated that the viral protease nsp5 can functionally repress p53 by interfering with its transcriptional activity, and has suggested p53 as an “intrinsic host restriction factor for the virus” ( 6 ). Similarly to Ma-Lauer, they have also observed that the overexpression of p53 significantly reduced virus production, sustaining the hypothesis of a fundamental role of p53 in managing the cellular antiviral defenses.…”
Section: Introductionmentioning
confidence: 99%
“…One of the targets of the virus that plays an important role both in the mechanisms of innate immunity and in the control of the cell cycle and other pathways that regulate cell replication, damage repair, apoptosis and metabolism is the p53 protein ( Cardozo and Hainaut, 2021 ; Ma-Lauer et al, 2016 ; Zauli et al, 2020 ; Harford et al, 2022 ; Kumar et al, 2022 ; Zauli et al, 2022 ). Indeed, the tumor suppressor p53 is a pleiotropic protein controlling cell homeostasis and cell response to stress events, deciding cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the viral Papain-Like Proteases (PLPs) act directly on MDM2 and on RING finger and CHY zinc finger domain-containing protein 1 (RCHY1) the “core” ubiquitin ligases involved in p53 ubiquitination, promoting their stabilization, and forwarding p53 to the proteasome degradation ( Ma-Lauer et al, 2016 ; Yuan et al, 2015 ). Moreover, viral Non-Structural Protein 5 (NSP5) can interfere with p53 transcriptional activity, impacting the regulation of its target genes ( Kumar et al, 2022 ). Vice versa, overexpression of recombinant TP53 gene has shown some capacity to moderate SARS-CoV replication ( Ma-Lauer et al, 2016 ; Kumar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%